Comprehensive Review of Healthcare Disparities, Accessibility, and Quality Improvement Strategies - Al-Harbi, Abdullah Rashid Sayer; Al-Mutairi, Ahmed Obaidullah Awad; Alharbi, Rakyan Saad Awad; Al-Muhaisin, Saleh Abdullah; Al-Harbi, Mohammed Saleh; Al mautairi, Abdulaziz Fahad Masha; Al-Harbi, Al-Humaidi Abdullah Qablan; Al harbi, Saleh Sanat Naqi; Alharbi, Mohammed Rashed S; Al Ogayyel, Mohammed Khalifah (Journal of Ecohumanism, 2024)
Since healthcare disparities have become one of the most significant issues globally, the availability and quality of healthcare are highly affected. These variations depend on many factors, such as socioeconomic level, race, region, and healthcare system organization. Though much has been done to overcome these disparities, both access to care and quality of care worsened among marginalized groups, consequently resulting in poorer health among these groups. The following review critically analyzes the principal determinants of healthcare inequalities, especially healthcare access and qualitative improvement. It also assesses the current worldwide approaches to alleviate such disparities and offers a detailed outlook on healthcare challenges and the prospects for enhancement.